2000
DOI: 10.1146/annurev.publhealth.21.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Genetics: An Emerging Interdisciplinary Field for the Post-Genomic Era

Abstract: Key Words public health research ethics, environmental/genetic interactions, hemochromatosis, community-based research s Abstract Public health genetics is an exciting interdisciplinary area that brings all the public health sciences to bear on the emerging challenge of interpreting the medical and public health significance of genetic variation within populations. Sequencing of the human genome will generate an avalanche of genetic information to be linked with information about microbial, chemical, and physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…However, questions remain about how to integrate genomic medicine into clinical practice, such that patients reap the greatest possible benefits from increased understanding about the role of genetics in the conditions they live with or for which they are at risk. Many commentators have suggested that perhaps the optimal strategy for effective integration of genomics into all aspects of healthcare is to develop interdisciplinary collaborations between genetic counselors and physicians, including those engaged in family practice as well as specialists (Omenn, 2000;Greendale and Pyeritz, 2001;Guttmacher et al, 2001;Erskine et al, 2013;Austin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, questions remain about how to integrate genomic medicine into clinical practice, such that patients reap the greatest possible benefits from increased understanding about the role of genetics in the conditions they live with or for which they are at risk. Many commentators have suggested that perhaps the optimal strategy for effective integration of genomics into all aspects of healthcare is to develop interdisciplinary collaborations between genetic counselors and physicians, including those engaged in family practice as well as specialists (Omenn, 2000;Greendale and Pyeritz, 2001;Guttmacher et al, 2001;Erskine et al, 2013;Austin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The introductory article described public health genetics as an emerging interdisciplinary field for the postgenomic era (15). Other articles in that symposium addressed host-pathogen interactions in emerging and re-emerging infectious diseases (11); nutrition, genetics, and risks of cancers (19); the scientific underpinnings for population screening for hereditary hemochromatosis (12); and research and educational challenges in the interface of genetics and public health (2).…”
Section: Introductionmentioning
confidence: 99%
“…Other articles in that symposium addressed host-pathogen interactions in emerging and re-emerging infectious diseases (11); nutrition, genetics, and risks of cancers (19); the scientific underpinnings for population screening for hereditary hemochromatosis (12); and research and educational challenges in the interface of genetics and public health (2). We also highlighted the genetics of unhealthful behaviors, especially smoking and alcoholism, and ethical issues and principles for community-based research (15).…”
Section: Introductionmentioning
confidence: 99%
“…3 The programs are now a prototype for population genetic screening programs. However, recent genetic research is making a substantial impact on health improvement and disease prevention, 4 and review of current practices in offering population genetic screening programs is appropriate.…”
mentioning
confidence: 99%